Good Cop, Bad Cop: Quality of Parental Involvement in Type 1 Diabetes Management in Youth - Young, Mackenzie T. (Curr Diab Rep, 2014)
Sustained parental involvement in diabetes management has been generally advised to counteract the deteriorating adherence and glycemic control often seen during adolescence, yet until recently, little attention has been given to the optimal amount, type, and quality of parental involvement to promote the best health outcomes for adolescents with type 1 diabetes (T1D). This review synthesizes research regarding the involvement of caregivers—primarily mothers and fathers—of youth with T1D, with a focus on biopsychosocial outcomes. The recent literature on parental involvement in diabetes management highlights a shift in focus from not only amount but also the types (e.g., monitoring, problem-solving) and quality (e.g., warm, critical) of involvement in both mothers and fathers. We provide recommendations for ways that both parents can remain involved to facilitate greater collaboration in shared direct and indirect responsibility for diabetes care and improve outcomes in youth with T1D.